Early pregnancy diagnosis in beef cattle through the expression of Interferon-tau stimulated genes in peripheral blood polymorphonuclear cells - Melo, Gabriela Dalmaso de (2019)
Considering that interferon-tau (IFNT) can stimulate several transcripts (ISGs) in mono (PBMCs) and polymorphonuclear cells (PMNs) at the maternal peripheral circulation, here we tested the central hypothesis that ISGs expression in PMNs would occur earlier and more intensely, which would allow a more accurate pregnancy diagnosis. This dissertation consists of two studies. In the first study, we compared the transcript abundance of ISGs (ISG15, OAS1, MX1 and MX2) and IFNT type 1 receptors (IFNAR I and II) in PMNs and PBMCs of pregnant (n=8) and non-pregnant (n=9) inseminated Nelore heifers, from D0 (FTAI) to day D20. In this study, we concluded that PMNs do not respond earlier to the conceptus stimuli, and ISG15 and OAS1 expression both in PMNs and PBMCs can be used as a suitable marker for pregnancy diagnosis on D18 and D20 post-FTAI. Also, gestational status and cell type do not affect IFNAR I and II expression. In the second study, we compared the abundance of ISG15 and OAS1 in PMNs on D20 post-FTAI in Nelore heifers (n=103) and cows (n=144) as pregnancy predictors to the diagnosis performed by Doppler ultrasonography (Doppler-US) and measurement of peripheral plasma progesterone (P4) on D20, and measurement of pregnancy-associated glycoproteins (PAGs) on D25 post-FTAI. Females were artificially inseminated on D0. Pregnancy was diagnosed by B-mode ultrasonography on D30 and D70, and after the final diagnosis, females were divided in four groups: Pregnant; Non-pregnant; Functional CL but non-pregnant (CL-NP) and Pregnancy loss (PL). After determining cutoff values through a ROC curve, the Sensitivity (SE), Specificity (SP), Positive Predictive Value (PPV), Negative Predictive Value (NPV) and Accuracy (ACC) were determined for each method. All the methods evaluated were significant (P<0.0001) predictors of pregnancy, but better accuracies were obtained through PAGs and P4 concentrations, and Doppler-US, due to the lower number of false positive and false negative results. We concluded that, despite being significant pregnancy markers, the practical execution of a pregnancy diagnosis through ISGs abundance in PMNs is still not viable due to the considerable number of false-positive and false-negative results. The determination of PAGs and P4 concentrations and luteal blood perfusion by Doppler-US offer better accuracies. The Doppler-US and P4 methods can be performed earlier, but a real-time diagnosis is only possible by Doppler-US.